Professional Communication - Noor Azlin, Bidin; Safiah , Sidek; Nor Hazlen Niza , Hussein (Pearson, Prentice Hall, 2007)
This book is designed to help students develop and sharpen their skills in technical communication, which primarily focuses on writing reports, job seeking strategies, meetings, and making oral presentations. All these are indeed important for the students whose careers will involve making complex scientific and technical information accessible to a variety of audiences (including non-technical, lay audiences). For these students, the concepts in this book would be extremely useful in terms of how to present expert knowledge to general as well as specific audiences.